2021
DOI: 10.3390/ijerph18073555
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Biofilm and Bacteriology in Otitis Media with Effusion in Children: A Prospective Cross-Sectional Study

Abstract: Background: Otitis media with effusion (OME) can cause serious complications such as hearing impairment or development delays. The aim of the study was to assess the microbiological profile of organisms responsible for OME and to determine if a biofilm formation can be observed. Methods: Ninety-nine samples from 76 patients aged from 6 months to 12 years were collected for microbiological and molecular studies. Results: In microbiological studies, pathogenic bacteria Haemophilus influenzae (38.89%), Streptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Most of the samples analyzed are from OME cases (85.71%). Therefore, the identification of H. influenzae as the most prevalent pathogen in the MEF agrees with other studies that report H. influenzae as the predominant pathogen in OME [8,14,35]. However, the reported prevalence rates are highly variable due to different health care programs, particularly vaccination, in various geographical locations [36].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most of the samples analyzed are from OME cases (85.71%). Therefore, the identification of H. influenzae as the most prevalent pathogen in the MEF agrees with other studies that report H. influenzae as the predominant pathogen in OME [8,14,35]. However, the reported prevalence rates are highly variable due to different health care programs, particularly vaccination, in various geographical locations [36].…”
Section: Discussionsupporting
confidence: 89%
“…The fact that most children were immunized with a pneumococcal conjugate vaccine possibly contributed to a lower incidence of S. pneumoniae. The identification of S. aureus in 42.86% of samples may look somewhat surprising, but a recent study also reports a high prevalence (27.78%) of S. aureus in MEF samples from OME cases [14]. Nevertheless, differences in pathogens' prevalence in studies conducted in the same country have been observed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with previous publications, this study also demonstrated that RT-PCR was more sensitive than traditional culture techniques to the detection of bacterial otopathogens ( Ngo et al, 2016 ). This is due to the organism's fastidious growth requirements and the presence of viable organisms within a biofilm, which reduce the sensitivity of detection using culture ( Thornton et al, 2013 ; Niedzielski et al, 2021 ). In the current study, which was undertaken when the children were well, it is not possible to differentiate whether the magnitude of the difference between RT-PCR and culture results was technical or due to a lower bacterial load at the time of sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, bacteria-induced meningitis has a cytotoxic effect on the cochlea and may lead to neural damage (73). In addition, even the middle ear can be affected by bacterial-induced inflammatory processes, of which otitis media with effusion and chronic suppurative otitis media are the most severe forms (74,75).…”
Section: Involvement Of Mirnas In Ear Infection and Inflammatory Proc...mentioning
confidence: 99%